Effect of Covid 19 on Mental Health and Coping Strategies: A Bibliometric Analysis using Scopus Database (Journal of Namibian Studies : History Politics Culture, 2022)
Purpose – Coronavirus disease has resulted in an unexpected negative situation globally, impacting physical and psychological distress among people leading to various psychological problems. This study has been undertaken to comprehensively examine current research about the effect of COVID-19 on mental health of people in general and strategies adopted to recover. This study involves bibliometric analysis of available research work on Scopus data base on the selected theme using 355 documents as a sample for the analysis.  The results affirmed that the mental well-being of individuals worldwide has been impacted by the loss of loved ones, financial setbacks resulting from job cuts, and the experience of isolation. The findings may help researchers and academicians better understand the research in the area of managing mental health during trying times. The study can be extended to structured literature review which will provide better insight into the methods or techniques used by people with varying demographics while coping with mental health issues.